Teaching NeuroImage: Traumatic Dissection of Lenticulostriate Arteries Within an Enlarged Perivascular Space. (1st March 2022) - Janvier, Paul; Kerleroux, Basile; Varlan, David; Rodriguez-Régent, Christine; Trystram, Denis; Allard, Julien; Drai, Maxime; Oppenheim, Catherine; Ben Hassen, Wagih; Naggara, Olivier
Abstract : A 33-year-old woman was admitted with right side hemiplegia after head trauma. Brain MRI revealed an acute ischemic stroke in the left lenticulostriate territory and a parenchymal hematoma (Figure 1). The hematoma occurred within an enlarged perivascular space (PVS), which had been incidentally discovered 10 years earlier. 1, 2 It was suspected that a traumatic dissection of lenticulostriate arteries within the PVS was responsible for both ischemic and hemorrhagic events (Figure 1). Healing of the hematoma and disappearance of the PVS and the lenticulostriate arteries were observed 2 months later (Figure 2). Excessive mobility of lenticulostriate arteries within an enlarged PVS may explain the mechanism of traumatic dissection in this case.